2020
DOI: 10.1039/c9cp06175d
|View full text |Cite
|
Sign up to set email alerts
|

Influence of nonmetal dopants on charge separation of graphitic carbon nitride by time-dependent density functional theory

Abstract: Photocatalysts are crucial materials for green energy production and environmental purification. Non-metal doped graphitic carbon nitride (g-C 3 N 4 ) has attracted much attention in recent years because of low-cost and desired photocatalytic performance characteristics such as high charge separation efficiency and broad visible light absorption. In this study, we used time-dependent density functional theory and wave function analysis to evaluate the charge separation characteristics of phosphorus-, oxygen-a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 64 publications
0
9
0
Order By: Relevance
“…Armed with the results presented herein, the preferred sites for the HER and OER are identified and generally correspond to the nitrogen atoms (or HOMO) and carbon atoms (or LUMO), respectively. The results presented in this work also provide the most suitable sites for chemical doping studies involving g -C 3 N 4 building blocks, where modifications of the electronic structure are essential to achieve a given set of desired properties . Likewise, this study is ongoing and will be followed up by systematic doping studies of the n -mel and n -hept monolayers identified in this work.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…Armed with the results presented herein, the preferred sites for the HER and OER are identified and generally correspond to the nitrogen atoms (or HOMO) and carbon atoms (or LUMO), respectively. The results presented in this work also provide the most suitable sites for chemical doping studies involving g -C 3 N 4 building blocks, where modifications of the electronic structure are essential to achieve a given set of desired properties . Likewise, this study is ongoing and will be followed up by systematic doping studies of the n -mel and n -hept monolayers identified in this work.…”
Section: Discussionmentioning
confidence: 86%
“…The results presented in this work also provide the most suitable sites for chemical doping studies involving g-C 3 N 4 building blocks, where modifications of the electronic structure are essential to achieve a given set of desired properties. 93 Likewise, this study is ongoing and will be followed up by systematic doping studies of the n-mel and nhept monolayers identified in this work.…”
Section: ■ Conclusionmentioning
confidence: 98%
“…The peak at around 455 nm decreased significantly with increasing phosphorus doping (Figure S4a–c), in agreement with the above argument that charge recombination is inhibited because extra donor states are created by the P 2p levels as a result of P-doping. Additionally, the previous study demonstrated that phosphorus doping in g-C 3 N 4 could not only improve the charge separation but also reduce the overlap and lengthen the distances between electron–hole pairs compared to the use of oxygen or sulfur as dopants. , …”
Section: Resultsmentioning
confidence: 99%
“…Subsequently, Pdoped triazole-based g-C 3 N 5 was produced through condensation polymerization via the elimination of HCl and NH 3 at a temperature of approximately 550 °C. Based on the XPS results, the P-substitution at C sites was randomly distributed throughout the structure; this substitution would not only result in more electron donation but also attract photoexcited charges 21 to enhance the photocatalytic activity.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation